Indonesia PENERAPAN DECISION SUPPORT SYSTEM PADA E-KATALOG PEMILIHAN WARNA CAT DENGAN METODE SAW BERBASIS ANDROID - Febrianti, Eka Lia; Pernando, Yonky; Verdian, Ihsan; Syafrinal, Ilwan; Roza, Yuni (JURSIMA, 2022)
To operate in a business system, a company must have a good mastery of knowledge about its customers, products and services. Product information that is clearly stated is the main basis of the business system. Decision support systems that are enriched with clear product information can increase customer satisfaction with the company's products and services. Product information consists of paint color and paint type. This decision support system is designed to be a knowledge base of paint, paint color, paint type and search for the type of paint that customers are looking for. In this Final Project, the author will create a decision support system using the SAW method and an electronic catalog (E Catalog) using the Android Studio application and using the waterfall method. This decision support system can help customers to choose the type of paint based on product quality. This decision support system will be a system with various types of paint according to customer needs with a list of paint colors according to customer needs to increase customer satisfaction